2021
DOI: 10.1111/jre.12846
|View full text |Cite
|
Sign up to set email alerts
|

The role of CRISPR‐Cas in advancing precision periodontics

Abstract: The significant advancement of molecular biology has revolutionized medicine and provided important technologies to further clinical research development. Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) are DNA sequences derived from bacteriophages which have previously infected the bacterial species. The CRISPR–Cas system plays a key role in bacterial defense by detecting and destroying DNA fragments during subsequent bacteriophage invasions. The Cas9 enzyme recognizes and cleaves new invad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
0
2
0
1
Order By: Relevance
“…Notably, preclinical and clinical investigations have demonstrated promising outcomes with this approach in developing new cancer therapies. Additionally, recent studies underscore CRISPR-Cas9’s potential in identifying oral cancer-associated genes and its broader applications in precision dentistry, affirming its significant promise in oral cancer management ( 75 ).…”
Section: Unveiling the Potential Of Crispr/cas9 In Oral Cancer Therapymentioning
confidence: 99%
“…Notably, preclinical and clinical investigations have demonstrated promising outcomes with this approach in developing new cancer therapies. Additionally, recent studies underscore CRISPR-Cas9’s potential in identifying oral cancer-associated genes and its broader applications in precision dentistry, affirming its significant promise in oral cancer management ( 75 ).…”
Section: Unveiling the Potential Of Crispr/cas9 In Oral Cancer Therapymentioning
confidence: 99%
“…It was documented that knocking out the PTPN2 gene with CRISPR–Cas9 in mouse models enhances the phosphorylation of JAK1 and STAT3,22 transcription factors, leading to increased periodontal inflammation. Therefore, it can be concluded that PTPN2 contributed to the inhibition of this inflammation [ 137 139 ]. Overall, the usage of the CRISPR method in periodontitis experimental trials has been limited; however, with the development of this system, more therapeutic strategies will replace surgery to treat periodontal disorders.…”
Section: Clinical Applications Of the Crispr Systemmentioning
confidence: 99%
“…Dette kan vaere molekyler som øker/hemmer inflammasjon eller kan ha andre effekter i patogenesen. Detaljert kunnskap om dette kan danne grunnlag for målrettet og persontilpasset behandling (presisjonsmedisin) av sykdommer som periodontitt, på engelsk kalt «precision periodontics» (24,25).…”
Section: Crispr-cas Som Redskap I Immunmoduleringunclassified